PATTERNS OF CREATIVITY TRENDS AMONG HEALTH MANAGERS IN HEALTH SECTOR OF SAUDI ARABIA, RIYADH REGION - Al Shehri, Othman Ali M.; AlHarthi, Ayedh Saud; Al-Khatib, Ahed J. (European Scientific Journal, ESJ, 2013)
Introduction: creativity is concerned with coping of daily challenges and can be performed by managers and employees to achieve the goals of organization. Study objectives: To Identify the level of creativity among health managers in health sector of Saudi Arabia, to examine the relationship between gender, educational level, specialty and age, with the level of creativity among health managers in health sector of Saudi Arabia and to identify the differences in level of creativity among health managers of Saudi Arabia between male and female, with different specialties and with different educational levels. Methodology: Study design and setting: Cross-sectional study design. The present study was conducted at the different departments at King Saud medical City, Prince Salman Hospital, Al- Gawieiah Hospital, Al-Amal Hospital, Al-yamama Hospital, Al-Dawadmi Hospital and Saudi ministry of health. A convenient sample of 175 participants was included in the study. A previously validated questionnaire was used to gather data from participants. Results: The data showed that age, sex and income were not correlated significantly with all domains of creativity. Educational level was correlated significantly with work environment and creativity potential. Conclusion: Demographical variables did not show a significant correlation with all domains of creativity (p value >0.05) except educational level which was significantly correlated with work environment (p value 0.004) and creativity potential (p value 0.000).